THE EFFECT OF AUDIT QUALITY ON EARNINGS MANAGEMENT (STUDY IN CONSUMER GOODS SECTOR COMPANIES WHICH LISTED ON THE INDONESIA STOCK EXCHANGE IN 2015-2016) - Ina, Ina (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2018)
The purpose of this research is to analysis and provide empirical evidence about the relationship between audit quality on earnings management and answer the research result are inconsistent regarding the relationship between audit quality on earnings management. Auditor quality in this study use size of audit firm and industry specialist auditor. The modified Jones model is used to measure discretionary accruals (the proxi for earnings management). This study uses secondary data from annual reports of consumer goods sector companies which listed on Indonesia stock exchange (idx) in 2015-2016. The method of data collection is purposive sampling method and resulted 54 firm observation. The analysis technique in this study uses a multiple regression analysis with help from a program named SPSS. The results indicate that audit firm size had no significant effect to earnings managementand industry specialist auditor had significant effect to earnings management.Keywords: Audit quality, Earnings management, size of auditor firm, auditor industry specialization